The International Summer School on “The Role of Informality in Socio-Economic Transition Environments” - Di PuppoLili (Экономическая социология, 2014)
The International Summer School on “The Role of Informality in Socio-Economic Transition Environments”, organized by the National Research University Higher School of Economics (HSE) in cooperation with Freie Universität (FU) Berlin, was held from 30 June to 6 July, 2014 at the Moscow campus of HSE. The Summer School brought together 20 students from both of the sponsoring institutions, as well as from other European universities, around a rich programme of lectures given by HSE and FU Berlin faculty. The lectures covered various aspects of informality such as informal entrepreneurial activity, corruption in transition societies, informal political action and social networks, as well as methods for their study, ranging from ethnographic methods to lab experiments on police corruption. The students were organized into three working groups to study informality in more depth. Each working group focused on one of the following topics: corruption in (higher) education, informality in the labor market and violent pressure on businesses. The working groups met with experts at HSE Moscow research centers, and at the conclusion of the Summer School made a presentation of their findings. The Summer School shows how a rich research agenda can emerge from bringing together perspectives from Russia and Germany as well as other West European countries on the field of informality.